Zarkasha - Shoroq Marshoud; Noura Abu-hashua; Haneen Nidal (My University, 2016)
Over time, humans need for clothing was onlyas all the necessities of life including food or shelter . it has been associated with the need for prevention of weather conditions such as a cold and heat. The dress has evolved from being just the skins of animals and their wool and their fur and feathers to clothes sewed with so many patterns , models and types . The world of clothing is always changing, as new cultural influences meet technological innovations. People throughout the world also view clothing as a reflection of current fashion trends within a culture.. Wearing certain colors, brands and types of clothing allows an individual to affiliate himself with a particular group. Since clothing can be influential in a persons life at any age, so the need of dressing well has became necessity! So in order to get the perfect matched outfit, dress well and be unique, there became a need for an application to fulfil this desire. The main goal of Zarkasha is to help the user to achieve the outfit he/she desire, to show up their style and personality, by help the user with getting matching suggestion on a particular clothing item to get unique, perfect and special outfit.

.
Zarkasha